Technological, rheological and sensory characterizations of a yogurt containing an exopolysaccharide extract from Lactobacillus fermentum Lf2, a new food additive. (December 2016) - Ale, Elisa C.; Perezlindo, Marcos J.; Pavón, Yanina; Peralta, Guillermo H.; Costa, Silvia; Sabbag, Nora; Bergamini, Carina; Reinheimer, Jorge A.; Binetti, Ana G.
Abstract: Lactobacillus fermentum Lf2, an autochthonous strain isolated as a non starter culture in Cremoso cheese, produces high EPS levels (~ 1 g/L) in optimized conditions (SDM broth, pH 6.0, 30 °C, 72 h). Technological (texture profile and rheological analysis) and sensory properties of non-fat yogurts with 300 and 600 mg EPS/L were studied at 3 and 25 days after manufacture. Yogurts with different EPS concentrations showed higher hardness values than the control group at both periods of time, being the only significant difference that remained stable during time. The consistency index was also higher for the treated samples at both times evaluated, being significantly different for samples with 300 mg/L of EPS extract, while the flow behavior index was lower for EPS-added yogurts. The thixotropic index was lower (P < 0.05) for samples with the highest EPS extract concentration at the end of the storage time. Regarding the sensory analysis, those yogurts with 600 mg/L of EPS extract presented the highest values of consistency at 3 days of storage. No considerable differences for defects (milk powder, acid, bitter and cooked milk flavors) were perceived between treated and control samples at both times evaluated. Syneresis was also studied and samples with 600 mg/L of EPS extract presented the lowest syneresis values at 25 days of storage, which considerably decreased with the time of storage. In conclusion, the EPS from L. fermentum Lf2, used as an additive, provided yogurt with creamy consistency and increased hardness, without the presence of unwanted defects and improving the water holding capacity of the product. All the analysis done showed the potential of this extract to be used as a technofunctional natural ingredient, and it should be considered its positive impact on health, according to previous studies. Graphical abstract: Highlights: Lactobacillus fermentum Lf2 is able to produce high levels of EPS under controlled conditions. EPS from  Lactobacillus fermentum  Lf2 provided yogurt with creamy consistency and increased hardness without unwanted defects. The addition of EPS improved the water holding capacity of the yogurt.